2006
DOI: 10.1002/jpln.200521765
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization and nitrate leaching into groundwater on arable sandy soils

Abstract: Nitrate leaching depending on N fertilization and different crop rotations was studied at two sites with sandy soils in N Germany between 1995 and 2000. The leaching of NO À 3 was calculated by using a numerical soil-water and N model and regularly measured N min values as input data. Also the variability of N min values on the sandy soils was determined along transects. They reveal the high variability of the N min values and show that it is not possible to confirm a significant N min difference between ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 25 publications
3
36
0
3
Order By: Relevance
“…In autumn, 37.1-45.4% of the annual amount of nitrogen is leached, so the rainier is the autumn the higher nitrogen content is leached from the upper soil layer. The established pattern confirms scientists' recommendations to reduce the infiltration from agricultural soils through autumn period by cultivating cover crops (Vos, van der Putten, 2004;Köhler et al, 2006;Jayasundara et al, 2007).…”
Section: Resultssupporting
confidence: 76%
“…In autumn, 37.1-45.4% of the annual amount of nitrogen is leached, so the rainier is the autumn the higher nitrogen content is leached from the upper soil layer. The established pattern confirms scientists' recommendations to reduce the infiltration from agricultural soils through autumn period by cultivating cover crops (Vos, van der Putten, 2004;Köhler et al, 2006;Jayasundara et al, 2007).…”
Section: Resultssupporting
confidence: 76%
“…It concurs with published literature as a potential issue throughout Europe, including the northern and central case study MSs: the UK [46], Sweden [47], Poland [48], France [49], northern Spain [50,51] and Germany [52]. Italy [53,54] and Greece [55] in the south also report NO 3 ¡ leaching from cultivated land, a factor further influenced by irrigation during drier periods of the year [56].…”
Section: ¡1supporting
confidence: 88%
“…According to model calculations of Springob et al [14] and Springob and Kirchmann [15], it was estimated that it might take up to 100 years for the soils to achieve a new equilibrium under the present conditions. Under these conditions, Köhler et al [16] concluded that the only way to reduce the N output to groundwater is to convert the arable land into forests or back into continuous grasslands, while setting aside the land will not reduce the risk of nitrate leaching in the long run. However, another promising land-use for fallow grounds to meet the requirements of groundwater protection might be the establishment of SRC with fast-growing trees like poplar or willow.…”
Section: Introductionmentioning
confidence: 99%